2016
DOI: 10.1289/ehp.1409437
|View full text |Cite
|
Sign up to set email alerts
|

Radon Exposure, IL-6 Promoter Variants, and Lung Squamous Cell Carcinoma in Former Uranium Miners

Abstract: Background: High radon exposure is a risk factor for squamous cell carcinoma, a major lung cancer histology observed in former uranium miners. Radon exposure can cause oxidative stress, leading to pulmonary inflammation. Interleukin-6 (IL-6) is a pro-carcinogenic inflammatory cytokine that plays a pivotal role in lung cancer development. Objectives: We assessed whether single nucleotide polymorphisms (SNPs) in the IL6 promoter are associated with lung cancer in former u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
(51 reference statements)
0
19
1
Order By: Relevance
“…Yngveson et al (1999) have shown that residential exposure to radon seems to contribute to a higher mutation prevalence of the TP53 gene in lung tumors, especially among nonsmokers. There are only few studies on radon exposure and gene poly morphisms (Bonner et al, 2006;RuanoRavina et al, 2014;Leng et al, 2016). Two of them provided evidence for an interaction between members of the glutathione Stransferase family GSTT1 (RuanoRavina et al, 2014) and GSTM1 (Bon ner et al, 2006;RuanoRavina et al, 2014) and radon in lung cancer risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yngveson et al (1999) have shown that residential exposure to radon seems to contribute to a higher mutation prevalence of the TP53 gene in lung tumors, especially among nonsmokers. There are only few studies on radon exposure and gene poly morphisms (Bonner et al, 2006;RuanoRavina et al, 2014;Leng et al, 2016). Two of them provided evidence for an interaction between members of the glutathione Stransferase family GSTT1 (RuanoRavina et al, 2014) and GSTM1 (Bon ner et al, 2006;RuanoRavina et al, 2014) and radon in lung cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Two of them provided evidence for an interaction between members of the glutathione Stransferase family GSTT1 (RuanoRavina et al, 2014) and GSTM1 (Bon ner et al, 2006;RuanoRavina et al, 2014) and radon in lung cancer risk. The association between IL-6 promoter SNPs and squamous cell carcinoma was studied in uranium miners (Leng et al, 2016). Choi et al (2018) identified that CHD4 rs74790047, TSC2 rs2121870, and AR rs66766408 are found to be common exonic mutations in both lung cancer patients and normal individuals exposed to radon indoors.…”
Section: Discussionmentioning
confidence: 99%
“…Genome damage, such as genome instability, was found in peripheral blood lymphocytes of lung cancer patients living in a region with high air pollution and increased background radon levels [ 5 , 20 ]. Moreover, IL-6 promoter variant was associated with lung cancer in uranium miners [ 21 ]. Reports show that caspase-3 is involved in cell apoptosis [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It might be informative to also conduct pilot studies in areas outside Western Europe, where workers have had higher levels of uranium exposure in recent years, but where more stringent standards (important to the conduct of ethical research) are being, or are about to be, implemented. As part of CURE, contacts have been established with research teams involved in research projects on uranium effects outside Europe: USA , Leng et al 2016, Kazakhstan (Kazymbet et al 2012) and Russia (Takhauov et al 2015). Conducting pilot molecular epidemiological studies in these countries would provide a wider, scientifically pertinent, perspective.…”
Section: Discussionmentioning
confidence: 99%